2018
DOI: 10.1002/nop2.138
|View full text |Cite
|
Sign up to set email alerts
|

Finnish healthcare professionals' attitudes towards robots: Reflections on a population sample

Abstract: AimTo answer the question: ‘How prepared healthcare professionals are to take robots as their assistants in terms of experience and acceptance?’BackgroundThe ageing population, increasing care needs and shortage of healthcare professionals pose major challenges in Western societies. Special service robots designed for care tasks have been introduced as one solution to these problems.DesignA correlative designMethodsEurobarometer data (N = 969) and survey data of nurses and other healthcare professionals (N = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 43 publications
5
55
0
2
Order By: Relevance
“…The resistance is related to organisational, cultural and technological as well as ethical issues [49]. It has even been suggested that professional caregivers have more concerns about robots than older adults [50] and the population in general [51]. Among the occupational groups, assistant nurses have been shown to be most reluctant regarding care robot use, while head nurses and other managers have the most positive view [51].…”
Section: Acceptance Of Care Robotsmentioning
confidence: 99%
“…The resistance is related to organisational, cultural and technological as well as ethical issues [49]. It has even been suggested that professional caregivers have more concerns about robots than older adults [50] and the population in general [51]. Among the occupational groups, assistant nurses have been shown to be most reluctant regarding care robot use, while head nurses and other managers have the most positive view [51].…”
Section: Acceptance Of Care Robotsmentioning
confidence: 99%
“…These lines of thinking could partially explain why surveys on the acceptance of, and positive and negative attitudes towards, robots in society tend to show lower acceptance for care robots compared to robots applied in other domains. For instance, 45 percent of the citizens in the EU28 countries felt at least moderately comfortable about the idea of having robots provide services or companionship to elderly or infirm people, whilst 61 percent were positive towards robots and artificial intelligence in general (Special Eurobarometer 460, 2017; for a recent study about healthcare professionals' attitudes toward robots, see Turja et al 2018).…”
Section: Demands Of Dignity In Robotic Carementioning
confidence: 99%
“…Naturally, the design of such assistive technology should ideally enhance rather than diminish the subjective feeling of self-respect. What is experienced as acceptable and subjectively enhancing varies contextually however (see Broadbent et al 2012;Turja et al 2018;Wu et al 2014).…”
Section: Own Actions and Attitudes: Self-respectmentioning
confidence: 99%
“…• After understanding the working of Nadine, they did not feel threatened about losing their jobs; instead, they highlighted that more social robots were needed to perform menial tasks in the service centre. The analysis of the insurance service agents also hints at a similar [26] positive result. In general, employee exposure to robots leading to optimistic attitudes could be something to explore in future research across populations.…”
Section: Discussionmentioning
confidence: 59%
“…Savela et al [10], who conducted a systematic literature review about social acceptance of robots in different occupation fields concluded that, when participants of a study were exposed to robots, positive attitudes occurred more frequently. However, this conclusion mostly stems from surveys in the healthcare [26] [27] and social services sectors. To the best of our knowledge, there has been no survey conducted among employees after they have seen a real robot work in their insurance service centre.…”
Section: Discussionmentioning
confidence: 99%